Pengaruh Kemampuan Individual Menilai Informasi Terhadap Minat Mahasiswa Akuntansi Dalam Menggunakan Internet Sebagai Sumber Pustaka Studi Kasus pada Universitas Bandar Lampung - Achmad Subing; Andrian K; Goenawan GOENAWAN (Jurnal Akuntansi dan Keuangan, 2011)
The purpose of the study is to analyze the influencing factors student intention to use the internet as a source or reference literature, namely the ability of the individual (computer self-efficacy and knowledge of search domain). This study uses TAM (Technology Acceptance Model) as a basic research model and incorporate TPB (Theory of Planned Behavior) to complete the TAM. Based on the problems and research objectives the research hypothesis posed is individual ability (computer self-efficacy and knowledge of search domain) in assessing influential information interests against positive and significant of accounting students using the internet as a source library with perceived of use for mediation. The method study is a study stastistical. Crystallization rate is formalized or explanatory research, which is a structured research began with the hypothesis put forward or by using questions. The method is a library and field research. The research literature (library) aims to find a theoretical basis supporting thisÂ  research, field research while aiming to obtain empirical data to test the hypothesis. Data obtained by distributing 100 questionnaires overall in the Faculty of Economics, University of Bandar Lampung Accounting Department and analysis of existing data is done with the help of SPSS version 17.